Feasibility of Cornstarch Masks for Dry Facial Skin Care - Mely Suryani Suryani; Prima Minerva (Jurnal Tata Rias dan Kecantikan, 2022)
This study is based on the problem of dry facial skin that causes a person's lack of self-confidence due to complaints of dark spots, dull, scaly skin, and fine wrinkles on the face. Corn is one of the vegetables that can be used as an ingredient for traditional skin beauty treatments and contains vitamin E which is beneficial for dry skin. The purpose of this study is to analyze the feasibility of cornmeal masks in terms of laboratory tests, organoleptic tests, hedonic tests This research method is an experiment and a type of quantitative descriptive research of cornmeal masks. Data collection methods in the form of observation, documentation, and questionnaires Research instruments are laboratory tests, organoleptic tests, hedonic tests and identification tests. The collected data is processed using a percentage descriptive analysis formula. The results of laboratory test studies are Vitamin A contained in cornmeal masks, namely 82 mg / 100gr, Vitamin B1 contained in cornmeal masks 5.5 mg / 100gr and Vitamin C contained in cornmeal masks 7.92 gr / 100gr. The results of the texture organoleptic test found that 86% of the panelists said the texture of cornmeal was very smooth, 100% of the panelists said the aroma of the cornmeal mask had a strong aroma typical of corn, 71% of the panelists said the stickiness of the cornmeal mask was quite close to the results of the hedonic test the panelists' likeness could be shown that 100% of the panelists liked the cornstarch mask. Flour Cornstarch masks have the feasibility for this to be used as a natural mask for treatment.